Augustine as Improvisational Theologian: The Musical Nature of Augustine's Thought - Crawford, Nathan (New blackfriars, 2016)
In this article, I explore the nature of Augustine's theological thinking. My thesis is that Augustine is an “improvisational theologian,” meaning his theology begins from the place that an improvisational musician's thinking does: attunement. In order to prove this thesis, I have three sections. The first is an analysis of the type of thinking that takes place in improvisational music, showing how it is predicated upon an idea of attunement. Second, I explore the improvisational nature of Augustine's thought by seeing how attunement is also at work in his thinking. In order to do this, I show how he develops a musical worldview in De Musica and how this guides his subsequent thinking in De Doctrina Christiana and Confessions. I conclude by briefly pointing to different contemporary theological issues that this reading of Augustine can enrich.